Administration of Nanovaccines by Transdermal Drug Delivery System-current and Future Perspectives - Shaik, Neelufar Shama (Asian Journal of Pharmaceutics (AJP), 2024)
Nanovaccines have emerged as a promising approach to enhance vaccination strategies, leveraging the power of nanotechnology to improve immune responses and vaccine efficacy. In recent years, the administration of nanovaccines through transdermal drug delivery systems has garnered significant attention. This review explores the research examples highlighting the utilization of transdermal drug delivery systems for nanovaccine administration. It discusses various nanovaccine delivery approaches, such as microneedle patches and lipidbased nanocarriers, and presents research studies demonstrating their efficacy and potential in immunization.